2022
DOI: 10.1111/bcpt.13738
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the GPR15 receptor‐mediated Gα protein signalling profile in recombinant mammalian cells

Abstract: The GPR15 receptor is a G protein-coupled receptor (GPCR), which is activated by an endogenous peptide GPR15L(25-81) and a C-terminal peptide fragment GPR15L(71-81). GPR15 signals through the G i/o pathway to decrease intracellular cyclic adenosine 3 0 ,5 0 -monophosphate (cAMP). However, the activation profiles of the GPR15 receptor within G i/o subtypes have not been examined. Moreover, whether the receptor can also couple to G s , G q/11 and G 12/13 is unclear. Here, GPR15L(25-81) and GPR15L(71-81) are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…3 We and others have found that upon GPR15L stimulation, GPR15 couples to the G i/o family decreasing intracellular 3 0 ,5 0 -cyclic adenosine monophosphate (cAMP) levels, recruits multifunction arrestin proteins and undergoes endocytosis. [3][4][5][6] GPR15 has been reported to be a potential therapeutic target for immune diseases such as colitis, dermatitis and multiple sclerosis. [7][8][9] Therefore, it is critical to understand the pharmacological and physiological functions of GPR15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We and others have found that upon GPR15L stimulation, GPR15 couples to the G i/o family decreasing intracellular 3 0 ,5 0 -cyclic adenosine monophosphate (cAMP) levels, recruits multifunction arrestin proteins and undergoes endocytosis. [3][4][5][6] GPR15 has been reported to be a potential therapeutic target for immune diseases such as colitis, dermatitis and multiple sclerosis. [7][8][9] Therefore, it is critical to understand the pharmacological and physiological functions of GPR15.…”
Section: Introductionmentioning
confidence: 99%
“…The full‐length GPR15L peptide contains two predicted protease cleavage sites, which leads to four potential endogenous variants, among them, the 11‐mer C‐terminal GPR15L(71‐81) peptide (coded as 01 ), which is the starting point of our study 3 . We and others have found that upon GPR15L stimulation, GPR15 couples to the G i/o family decreasing intracellular 3′,5′‐cyclic adenosine monophosphate (cAMP) levels, recruits multifunction arrestin proteins and undergoes endocytosis 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…While the full-length ligand demonstrates superior activation potency compared to GPR15L C11 (Supplementary Fig. S4a ), prior research has highlighted the pivotal role of the 11 amino acids located in the C-terminus for receptor recognition and activation 3 , 5 , 15 . We hypothesized that the N-terminal portion might participate in interactions with regions outside the orthosteric pocket of the receptor (pertaining to the interaction between chemokine C-termini and their receptors), potentially influencing ligand activation potency to some extent.…”
mentioning
confidence: 99%
“…We hypothesized that the N-terminal portion might participate in interactions with regions outside the orthosteric pocket of the receptor (pertaining to the interaction between chemokine C-termini and their receptors), potentially influencing ligand activation potency to some extent. However, truncating the C-terminal 11 amino acids from full-length GPR15L renders the peptide incapable of activating the receptor 3 , 15 , thereby affirming the essential role of interactions between GPR15L C11 and the orthosteric pocket of GPR15. Nonetheless, further investigations into the full-length structure of GPR15L are warranted to comprehensively elucidate its functional significance.…”
mentioning
confidence: 99%
“…It is a potential therapeutical target for immune and inflammatory diseases such as multiple sclerosis, HIV enteropathy, colitis, and dermatitis [24][25][26][27][28]. When the receptor is stimulated by its recently identified endogenous ligand, GPR15L(25-81) peptide, it activates G i/o proteins and inhibits the downstream second messenger (cAMP) effector adenylyl cyclase [29][30][31][32].…”
mentioning
confidence: 99%